2017
DOI: 10.3390/su9122316
|View full text |Cite
|
Sign up to set email alerts
|

Cover Crop Residue Amount and Quality Effects on Soil Organic Carbon Mineralization

Abstract: Decline in soil organic carbon (SOC) and the associated impacts on crop production under conventional farming raises concerns on how alternative management practices increase SOC sequestration and improve agricultural sustainability. This study aimed to understand SOC mineralization kinetics with different cover crop (CC) residue amendments. Soil samples were collected from a fallow and three CC (pea, oat, and canola) plots. Soil samples from the CC plots were manipulated with zero, five, and 10 Mg ha −1 of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 41 publications
4
50
0
5
Order By: Relevance
“…The integration of WCCs into cropping systems can increase ecosystem services and maximize the benefits provided by agricultural systems (Schipanski et al., ). Many of these benefits can be recognized through improvement of the soil, including erosion protection, improved aggregation, nutrient cycling, reduced compaction and an increase in soil organic carbon (SOC; Dabney, Delgado, & Reeves, ; Ghimire, Ghimire, VanLeeuwen, & Mesbah, ). Along with providing an abundance of soil services, WCCs can further aid in weed control, disease suppression, increased soil biological activity, increased water infiltration, and N‐fixation (Dabney et al., ; Marcillo & Miguez, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of WCCs into cropping systems can increase ecosystem services and maximize the benefits provided by agricultural systems (Schipanski et al., ). Many of these benefits can be recognized through improvement of the soil, including erosion protection, improved aggregation, nutrient cycling, reduced compaction and an increase in soil organic carbon (SOC; Dabney, Delgado, & Reeves, ; Ghimire, Ghimire, VanLeeuwen, & Mesbah, ). Along with providing an abundance of soil services, WCCs can further aid in weed control, disease suppression, increased soil biological activity, increased water infiltration, and N‐fixation (Dabney et al., ; Marcillo & Miguez, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the near future, it will be necessary to provide considerably more food and fiber with, at most, the same amount of resources as farmers today (Tilman, Balzer, Hill, & Befort, 2011). To continue to provide food and fiber to a growing population with limiting resources, agricultural organic carbon (SOC; Dabney, Delgado, & Reeves, 2001;Ghimire, Ghimire, VanLeeuwen, & Mesbah, 2017). Along with providing an abundance of soil services, WCCs can further aid in weed control, disease suppression, increased soil biological activity, increased water infiltration, and N-fixation (Dabney et al, 2001;Marcillo & Miguez, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that soil fertility is proportional to the soil microbial activity and SOM, as well as altering environmental conditions and land uses [47,48]. It has also been proved that crop residues and cover crops increase soil microbial biomass and activity and improve SOC sequestration in the long-term [49]. Therefore, cover crop residues stimulated cumulative carbon mineralization and improved SOC cycling in vineyard ecosystem, resulting in high level of BFI.…”
Section: Discussionmentioning
confidence: 96%
“…− and NH 4 + ] was determined by extracting 5-g soil subsamples in 25 mL 1-molar potassium chloride solution and analyzing in an automated TL-2800 single channel ammonia analyzer (Timberline Instruments, Boulder, CO, USA). For estimating PMC, 20 g soil subsamples were incubated for 28 days following the aerobic procedures described in detail in Ghimire et al [27]. The same incubated soil samples were subjected to estimate PMN using an automated TL-2800 single channel ammonia analyzer.…”
Section: Soil and Plant Sampling And Analysismentioning
confidence: 99%